Measure of processes of care (MPOC): Translation and validation for use in Korea. (17th June 2018) - An, M.; Kim, J. G.; Kim, J.
Abstract: Background: The measure of processes of care (MPOC) is a widely used instrument to assess parents' perception of the extent to which healthcare services they and their child receive are family centred. The purpose of this study was to examine the reliability and validity of the Korean translation of the MPOC (Korean MPOC). Methods: The Korean MPOC was completed by 198 parents of children receiving rehabilitation services in five provinces in South Korea. According to the Canadian validation procedures, analyses for internal consistency, construct and concurrent validity, and test–retest reliability were performed. Results: The Korean MPOC demonstrated adequate internal consistency, with Cronbach's alpha ranging from .85 to .98. Confirmative analyses of the scale structure support the construct validity of the Korean MPOC. The Pearson correlations r between the MPOC scale scores and Client Satisfaction Inventory score ranged from .60 to .83, supporting the concurrent validity of the Korean MPOC. The intraclass correlation coefficients were greater than .80 for all five scales, demonstrating good test–retest reliability. Conclusions: The Korean MPOC has good psychological properties and can be recommended for evaluation of processes of paediatric rehabilitation in Korea.